Fourwalkers, taildanglers, headhangers: labouring animals in Ulysses. Issue 2 (1st February 2022) - Adkins, Peter
ABSTRACT: This article takes as its broad premise two related questions: how does Ulysses register the animal labour from which modernity was produced? And, in turn, how do Joyce's textual innovations—his labouring of language—respond to the human-animal relationships that existed in early-twentieth-century Ireland? Although critics are increasingly attuned to the way in which Ulysses is a novel that teems with all sorts of animal life, less attention has been paid to the working animals whose presence would have been part of Joyce's everyday life; animals who are present on the pages of Ulysses in the form of draught horses and dairy cows, among others. Focusing predominantly on the figure of the horse, the species which played a central role in the production of the modern city and is perhaps the most frequently represented animal in Ulysses other than the human, this article will examine Joyce's alertness to the multispecies history of Irish modernity. Moreover, by looking at the formal innovations through which Joyce presents his equine figures—through, for instance, an instability of focalisation and an attention to material conditions—I will argue that Ulysses presents the subjectivity of both humans and nonhumans as produced through moments of affective entanglement. Highlighting moments of trans-species empathy that we find registered in the text's labouring of language, such as Bloom's encounter with the sweeper horse in 'Eumaeus' from which I take my title, this article will outline how working animals are integral to Joyce's task of presenting the everyday fabric of modernity, and that Ulysses demonstrates the ethical possibilities and, just as importantly, limitations that come with acknowledging such a fact.